Global and regional prevalence of vitamin D deficiency in population-based studies from 2000 to 2022: A pooled analysis of 7.9 million participants - Cui, Aiyong; Zhang, Tiansong; Xiao, Peilong; Fan, Zhiqiang; Wang, Hu; Zhuang, Yan (Frontiers in Nutrition, 2023)
Background Vitamin D deficiency has been considered a global health issue in recent years. However, there is still no study estimating the global and regional prevalence of vitamin D deficiency from 2000 to 2022. Methods We systematically searched Web of Science, PubMed (MEDLINE), Embase, Scopus, and Google databases on December 31, 2021, and updated them on August 20, 2022, without language and time restrictions. The studies investigating the prevalence of vitamin D deficiency in the general population were included. A standardized data extraction form was used to collect information from eligible studies. We used a random-effects meta-analysis to estimate the global and regional prevalence of vitamin D deficiency. We stratified meta-analyses by latitude, season, six WHO regions, the World Bank income groups, gender, and age groups. This study was registered with PROSPERO (CRD42021292586). Results Out of 67340 records searched, 308 studies with 7947359 participants from 81 countries were eligible for this study, 202(7634261 participants), 284(1475339 participants), and 165(561978 participants) studies for the prevalence of serum 25(OH)D < 30, < 50, and < 75 nmol/L, respectively. We found that globally, 15·7% (95% CrI 13·7–17·8), 47·9% (95% CrI 44·9–50·9), and 76·6% (95% CrI 74·0–79·1) of participants had serum 25-hydroxyvitamin D levels less than 30, 50, and 75 nmol/l, respectively; the prevalence slightly decreased from 2000–2010 to 2011–2022, but it was still at a high level; people living in high latitude areas had a higher prevalence; the prevalence in winter-spring was 1·7 (95% CrI 1·4–2·0) times that in summer-autumn; the Eastern Mediterranean region and Lower-middle-income countries had a higher prevalence; females and people aged 19-44 were vulnerable to vitamin D deficiency; gender, sampling frame, detection assays, sampling region, time of data collection, season, and so on contributed to heterogeneity between the included studies. Conclusion Globally, vitamin D deficiency remained prevalent from 2000 to 2022. The high prevalence of vitamin D deficiency would increase the global burden of disease. Therefore, governments, policymakers, health workers, and individuals should attach importance to the high prevalence of vitamin D deficiency and take its prevention as a public health priority.